2017
DOI: 10.1590/1808-057x201701980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of board interlocking on earnings management

Abstract: The participation of directors on more than one board is called "board interlocking". This phenomenon contributes to the spread of management and governance practices, through directors sharing their knowledge and experiences on other boards. Thus, directors could "carry" the earnings management practices present in one company into another in which they sit on the board. It is assumed that the greater directors' direct or indirect connections on boards, the greater the sharing of information, especially infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 56 publications
3
29
1
8
Order By: Relevance
“…In other hand, [22] found that shareholder-friendly corporate governance is related with higher systemic risk and stand-alone in the banking sector. [23] found that the greater the degree of centrality, the greater the EM, and that variation in negative and positive accruals is influenced by board intermediation. The core objective of [24] was to examine whether the BOD and other key committees influence earnings management through discretionary accruals.…”
Section: Literature Reviewmentioning
confidence: 96%
“…In other hand, [22] found that shareholder-friendly corporate governance is related with higher systemic risk and stand-alone in the banking sector. [23] found that the greater the degree of centrality, the greater the EM, and that variation in negative and positive accruals is influenced by board intermediation. The core objective of [24] was to examine whether the BOD and other key committees influence earnings management through discretionary accruals.…”
Section: Literature Reviewmentioning
confidence: 96%
“…In addition, the literature is not conclusive about the relationship between earnings management and corporate governance (Cunha & Piccoli, 2017;Erfurth & Bezerra, 2013;Lin & Hwang, 2010;Susanto & Pradipta, 2016;Zalata & Roberts, 2015). Largely due to the various metrics used.…”
mentioning
confidence: 99%
“…Lin and Hwang (2010) emphasize that corporate governance is a factor that is able to minimize the practice of earnings management, although there are some inconsistencies about this relationship (García-Meca & Sánchez-Ballesta, 2009). The relationship between earnings management and corporate governance occurs because corporate governance represents a set of mechanisms that contribute to the monitoring the managers (Cunha & Piccoli, 2017), limiting them and/or punishing them in certain accounting practices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…O valor dos accruals discricionários obtidos e sua análise tende a variar de acordo com o autor e o tipo de análise que este busca, assim, alguns estudos adotam o valor absoluto da variável de modo a avaliar a amplitude geral do gerenciamento de resultados (Martinez, 2010;Bao & Lewellyn, 2017;Joia & Nakao, 2014). Outros autores (Cunha & Piccoli, 2017;Martinez, 2008;Park & Shin, 2004) analisam a direção para a qual os resultados são gerenciados, avaliando o sinal obtido pela variável AD, assim, distinguem-se os accruals discricionários (AD) em AD Absolutos, AD Positivos (income increasing) e AD Negativos (income decreasing) (Silva, 2017).…”
Section: Análise De Robustezunclassified